Association of BMI with diet and physical activities of adult residence at Puncak Alam / Norazila Boimen, Nurul Salehah Bachok and Khairunnisa Abd Kahar - Boimen, Norazila; Bachok, Nurul Salehah; Abd Kahar, Khairunnisa (2016)
Background: To identify the association of body mass index (BMI), dietary habits and physical activity is one of the important components to give awareness to the public about the effect that may occur in the future. It is crucial for them to practice healthy habit as it can minimize chance of people to get diseases that encountered in unhealthy lifestyle. Objectives : The study aimed to assess the dietary habits, physical activity and their association with body mass index (BMI) among adult resident of Fasa 2 Puncak Alam. Methods: Descriptive quantitative cross-sectional study has been chosen to carry on this research. Participants were 300 adult residents at Puncak Alam Fasa 2, aged 16 to 60. Questionnaire was used as main research tool and data was collected between March until May 2016. The question survey involved 37 questions that consist about dietary habit, physical activity behavior and the perceived barrier included anthropometrics and demographics data. Body weight and height of the adult resident was measured and their BMI was calculated. Data was analyzing used SPSS statistical software 20.0, Chi-square test was used for testing significant of P value < 0.05. Results: Over 50.7% of respondent having normal weight, about 23.3% respondent was overweight and 12% are obese. Most of the respondent rate their "healthiness" of eating habits as "average" 50.7% (n=152) and only 1% (n=3) having "excellent" eating habits. Furthermore, 55%) (n=165) of the respondent reported that they did not exercise, while 45%) (n=135) were exercised. Out of the respondent whose did not exercise or exercise less than before mentioned that no time 64.3%) (n=193) as a barrier that prevented them from engaging in physical activity. Relating respondent BMI with dietary habits and physical activity revealed significant relation between "Dinner" (p = 0.001) and "Exercise since working", "Level of intensity" and "Type of exercise" (p = 0.031, 0.049 and 0.021 respectively). Conclusions: Respondent eating habit and physical activity is impacted by many factors. Prevention efforts should consider targeting factor such as their own belief and environment effect that make their behavior and habit are inadequately.